Resveratrol for cancer therapy: Challenges and future perspectives - Ren, Boxu; Kwah, Marabeth Xin-Yi; Liu, Cuiliu; Ma, Zhaowu; Shanmugam, Muthu K.; Ding, Lingwen; Xiang, Xiaoqiang; Ho, Paul Chi-Lui; Wang, Lingzhi; Ong, Pei Shi; Goh, Boon Cher (Cancer letters, 2021)
Resveratrol (3,4’,5-trihydroxy-trans-stilbene) has been expected to ameliorate cancer and foster breakthroughs in cancer therapy. Despite thousands of preclinical studies on the anticancer activity of resveratrol, little progress has been made in translational research and clinical trials. Most studies have focused on its anticancer effects, cellular mechanisms, and signal transduction pathways in vitro and in vivo. In this review, we aimed to discern the causes that prevent resveratrol from being used in cancer treatment. Among the various limitations, poor pharmacokinetics and low potency seem to be the two main bottlenecks of resveratrol. In addition, resveratrol-induced nephrotoxicity in multiple myeloma patients hinders its further development as an anticancer drug. New insights and strategies have been proposed to accelerate the conversion of resveratrol from bench to bedside. In the interim, the most promising approach is to enhance the bioavailability of resveratrol with new formulations. Alternatively, more potent analogues of resveratrol could be developed to augment its anticancer potency. Given all the gaps mentioned, much work remains to be done. However, if remarkable progress can be made, resveratrol may finally be used for cancer therapy. •Resveratrol attractive for treatment of colorectal and obesity-related cancers.•Poor bioavailability and low potency compromises anticancer activity of resveratrol.•Unconventional hermetic nature requires further investigation.